2020
DOI: 10.3390/ijms22010355
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation to Endoplasmic Reticulum Stress Enhances Resistance of Oral Cancer Cells to Cisplatin by Up-Regulating Polymerase η and Increasing DNA Repair Efficiency

Abstract: Endoplasmic reticulum (ER) stress response is an adaptive program to cope with cellular stress that disturbs the function and homeostasis of ER, which commonly occurs during cancer progression to late stage. Late-stage cancers, mostly requiring chemotherapy, often develop treatment resistance. Chemoresistance has been linked to ER stress response; however, most of the evidence has come from studies that correlate the expression of stress markers with poor prognosis or demonstrate proapoptosis by the knockdown … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 92 publications
0
11
0
Order By: Relevance
“…In this study, we compared two p53 mutant HNSCC cell lines, OECM1 and Detroit 562 cells, with different p53 mutations, and treated them with p73 activator(s). The Detroit 562 cell line has a p53 R175H mutation [17], and OECM-1 has a p53 V173L mutation [18]. We found that both RETRA and NSC59984 had a better cytotoxic response in OECM1 cells than in Detroit 562 cells.…”
Section: Introductionmentioning
confidence: 66%
See 1 more Smart Citation
“…In this study, we compared two p53 mutant HNSCC cell lines, OECM1 and Detroit 562 cells, with different p53 mutations, and treated them with p73 activator(s). The Detroit 562 cell line has a p53 R175H mutation [17], and OECM-1 has a p53 V173L mutation [18]. We found that both RETRA and NSC59984 had a better cytotoxic response in OECM1 cells than in Detroit 562 cells.…”
Section: Introductionmentioning
confidence: 66%
“…In this study, we found that two p73 activators, RETRA and NSC59984, have much higher cytotoxicity in OECM1 cells than in Detroit 562 cells (Figure 1). Detroit 562 cells have a p53 R175H mutation [17], and OECM-1 cells have a p53 V173L mutation [18]. The p73 specific downstream genes NEU4, JAG2, LIG1 and G6PD [21][22][23][24] were upregulated within RETRA-or NSC59984-treated OECM1 cells (Figure 2).…”
Section: P73 Activators Have Different Responses In Hnscc Cell Lines ...mentioning
confidence: 97%
“…The parental and cisplatin-resistant OECM1 cancer cell lines were grown in Roswell Park Memorial Institute Medium (RPMI; #11-100; Biological Industries, Beit Haemek, Israel) supplemented with 10% Fetal Bovine Serum (FBS; #10438-028; Thermo Fisher Scientific, Waltham, MA, USA), 1% penicillin-streptomycin (#15140-122; Thermo Fisher Scientific), and 1% glutamine. The characteristics of these cells were described in the previous study 18 Subculturing was performed using trypsin-EDTA. The medium was refreshed every 2 days.…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, this study also found that p53 nuclear translocation occurred in endoplasmic reticulum stress-adapted cells and that intracellular cisplatin uptake was not significantly different from control cells, but the accumulation of cisplatininduced DNA damage was dramatically reduced. Once p53 was knocked down, the cells could hardly tolerate prolonged ER stress and cisplatin treatment (25). This suggested that prolonged ER stress might counteract the effects of cisplatin by repairing DNA damage through the Polh-dependent TLS pathway, and inducing p53 nuclear translocation to make cells tolerate DNA damage.…”
Section: Molecular Basis Of Cisplatin Resistance In Oscc 21 Dna Damage Response and Cisplatin Resistance In Osccmentioning
confidence: 99%